Green Hospital Implementation in Indonesia: A Literature Review - Triansyah, Ade; Citra, Eka Widya; Tumbelaka, Benny; Lemba, Andy Khalidah; Stevani, Adisscka Beti; Ramadhani, Irani Nur; Nurhafida (Asian Journal of Healthcare Analytics, 2026)
Hospitals are highly resource-intensive institutions due to continuous clinical and administrative operations that require large amounts of energy, water, technology, and materials. This study reviews the implementation of green hospitals in Indonesia using a narrative literature review approach based on recent journal articles, policy documents, and WHO reports. The findings show that green hospital practices have developed mainly in waste management, energy efficiency, water conservation, and environmental governance. However, implementation remains uneven because of limited funding, weak interdepartmental coordination, inadequate monitoring systems, and low organizational commitment. Despite these barriers, green hospitals provide benefits such as operational efficiency, improved accreditation, enhanced institutional image, and better comfort for patients and staff. The study concludes that stronger leadership, standardized indicators, policy incentives, phased investment, and integration of environmental targets into hospital governance are essential for sustainable hospital transformation in Indonesia.